Tree Inventory and diversity analysis along a primary road in Palghar, Maharashtra , India - Joshi Nitesh; Mule Prachiti; Joshi Ambika (International Journal of Life Sciences, 2017)
Inventory of the arboreal cover occurring along a primary road in Palghar was prepared for understanding the diversity of the trees. During the survey 17 kilometres road was monitored which had two main types of land uses viz. Forest and urbanised area. Both the areas showed presence of different types of trees. A total of 97 tree species belonging to 33 different families with a count of 2052 were observed during the survey. Frequently distributed trees in forest area were Terminalia crenulata Roth., Butea monosperma (Lam.) Taub., Bombax ceiba Burm.f., Pterocarpus marsupium Roxb., Bridelia retusa (L.) A.Juss., Mitragyna parvifolia (Roxb.) Korth. while urbanised showed presence of Streblus asper Lour., Gliricidia sepium (Jacq.) Walp., Dalbergia lanceolaria L.f., Pithecellobium saman (Jacq.) Benth., Cassia siamea Lam., Delonix regia (Hook.) Raf., Peltophorum pterocarpum (DC.) K., Moringa oleifera Lam., Borassus flabellifer L., Mangifera indica L., Annona reticulata L., Annona squamosa L.